2003
DOI: 10.1177/1534735403259061
|View full text |Cite
|
Sign up to set email alerts
|

Mistletoe and Gemcitabine in Patients with Advanced Cancer: A Model for the Phase I Study of Botanicals and Botanical-Drug Interactions in Cancer Therapy

Abstract: Plant extracts of the European mistletoe (MTE), Viscum album, the most widely used cancer treatment in Germany, have been used in European countries as sole intervention or as adjunct to conventional cancer therapies for more than 80 years. Preclinical data suggest immunostimulatory and cytotoxic effects of MTE. While the clinical efficacy of MTE in cancer is being investigated, toxicity and potential interactions of MTE with standard chemotherapeutic agents are unknown. Gemcitabine is an approved antimetaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
40

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 52 publications
0
16
0
40
Order By: Relevance
“…11 prospective cohort studies [ 32 , 44 - 46 , 73 - 80 ] (Table 6 ) included 1,130 patients. Cancer sites studied were breast (n = 6), ovary (n = 1), CIN (n = 1), malignant pleural effusion (n = 2) and malignant ascites (n = 2).…”
Section: Resultsmentioning
confidence: 99%
“…11 prospective cohort studies [ 32 , 44 - 46 , 73 - 80 ] (Table 6 ) included 1,130 patients. Cancer sites studied were breast (n = 6), ovary (n = 1), CIN (n = 1), malignant pleural effusion (n = 2) and malignant ascites (n = 2).…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, studies have shown that the pharmacokinetics of gemcitabine, an antimetabolite chemotherapeutic agent, are not affected when combined with mistletoe therapy [64, 65]. The reduction in mistletoe ADRs during cotherapy with conventional drugs was probably due to the immunosuppressing nature of many of these therapies [62, 63], providing further evidence that mistletoe extracts are safe for use in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patients' Safety, Interactions: Additionally to the abovementioned results on AEs it seems necessary to point out that pharmacological studies on possible interactions with mistletoe therapy are widely lacking [84]. If in terms of QoL its main efficacy is in the area of immunomodulatory effects (cellular immunity) -next to psychological effects -an interaction with phase II enzymes seems unlikely, but nevertheless would have to be examined.…”
Section: Discussionmentioning
confidence: 99%